Pemanfaatan Wortel dan Kangkung pada Pembuatan Mie sebagai Diversifikasi Olahan Pangan Rumah Tangga di Lingkungan Perkotaan Yogyakarta - Sari, Yuli Perwita; Sudrajat, Ajat; Sambodo, Reo (Farmers: Journal of Community Services, 2024)
Noodles are much loved by the public and if product diversification is carried out, it can increase the nutritional content of the noodles. This service aims to provide knowledge about the processing of noodles given a mixture of carrots and kale in Patehan, Keraton, Yogyakarta City. This service has been carried out and attended by 20 participants. The method of implementation by providing education and practice directly. The implementation stage began with providing socialization and delivery of material on the use of carrots and kale in making noodles and ended with a question and answer session for participants and resource persons. Furthermore, the practice of making noodles by participants was carried out. The results of the service showed that participants' knowledge increased and could use carrots and kale for noodle making ingredients well and could produce healthy noodle products that are rich in nutrients. Noodle-making training using carrots and kale can improve the knowledge and skills of residents of Patehan, Keraton, Yogykarta. Keywords: Noodles, carrot, kale, diversification, Yogyakarta City